Pengaruh Pemberian Kapur Pada Air Gambut Terhadap Kelangsungan Hidup Dan Pertumbuhan Benih Ikan Gabus (Channa striata) - Shinta S Monalisa; Maryani Maryani; Kamisa Rumapea (Universitas Batangahari Jambi, 2021)
This research was conducted to determine the effect of giving different lime on the survival rate and growth of snack head seeds. This writing uses a completely randomized design (CRD) with 4 treatments and 3 replications. The hypothesis being tested was that the application of the limed lime had no significant effect on survival rate, the growth of snack head seed and the specific growth rate and lime administration differed significantly in feed conversion. The study was conducted at the Wet Aquaculture Laboratory, Palangka Raya University starting from February 3 - March 3, 2020. The results showed that the administration of different lime had no significant effect on survival rate, growth and specific growth rates but had a significant effect on feed conversion. The best survival rate of snack head seeds is in treatment D (250 g) that is equal to 57.73%, the best weight growth is in treatment C (200 G) that is equal to 3.16 grams, the best length growth is in treatment D (250 g) that is 2.57 cm, the best specific growth rate is in treatment D (250 g) which is 2.92% / day, and the best feed conversion value is in treatment D (250 g) which is 1.47%. Water quality such as temperature, acidity (pH) and dissolved oxygen (DO) are still in the normal range.